Short term outcomes of a new non-dissection minimally invasive surgery method for cystocele repair - G. Calongos; Y. Tsuji; Y. Ito; M. Handa; Y. Kubota; A. Ida (Clinical and Experimental Obstetrics & Gynecology)
Purpose of investigation: The objective of this study was to assess the safety and efficacy of our new surgical technique for cystocele treatment. Materials and Methods: Twenty patients diagnosed from May 2017 to October 2018 with a minimum stage III cystocele were included. Our new technique was performed bilaterally using two polypropylene monofilament suture threads. The suture started at the level of the left bulbo cavernosus muscle and continued to the right and then to the left uterosacral ligament. With the second thread, the suture was made on the opposite side to that described above. Patients were followed-up for a minimum of six months post-operatively (mean 9.9 months). Results: No intra-surgical or post-surgical complications were observed. Only one patient presented with a cystocele recurrence during follow-up, but did not require treatment. Conclusion: The new surgical technique was found to be safe and effective for cystocele repair in this study.